Hubungan Dukungan Keluarga Dengan Kepatuhan Minum Obat Pasien Tuberkulosis Pada Anak Di Kabupaten Wajo - Wardanengsih, Ery; Darwis, Nirmawati; Andi Mikhrunnisai (Innovative: Journal Of Social Science Research, 2025)
Treatment compliance is defined as the behavior of following all instructions and instructions given by health workers and the patient's own family to achieve the desired treatment results. Family support is a process that occurs throughout life. Family support allows families to function at different levels of intelligence and resourcefulness, improving family health and adaptability. This study aims to determine the relationship between family support and compliance with taking medication for tuberculosis patients in children in Wajo Regency. This type of research is quantitative using a descriptive analytical design with a cross sectional design. Data collection uses a questionnaire. The samples in this study were families with pediatric tuberculosis patients who received outpatient treatment in the working areas of the Tempe Health Center UPTD, Wewangrewu Community Health Center UPTD, and Tanasitolo Community Health Center UPTD, totaling 33 respondents taken using a purposive sampling technique. The data analysis technique uses chi-square. The results of this study indicate that there is a relationship between family support and compliance with taking medication in tuberculosis patients (P = 0.000 means α < 0.05). Based on this analysis, it can be concluded that there is a relationship between family support and compliance with taking medication for tuberculosis patients in children in Wajo Regency. The researcher's suggestion is that local health agencies are expected to provide education to tuberculosis patients and their families regarding preventing tuberculosis infection, as well as providing explanations so that affected individuals can receive tuberculosis treatment